Reprogramming of mPFC transcriptome and function in alcohol dependence. (24th November 2016) - Heilig, M.; Barbier, E.; Johnstone, A. L.; Tapocik, J.; Meinhardt, M. W.; Pfarr, S.; Wahlestedt, C.; Sommer, W. H.
Abstract : Despite its limited immediate reinforcement value, alcohol has a potent ability to induce neuroadaptations that promote its incentive salience, escalation of voluntary alcohol intake and aversion‐resistant alcohol seeking. A constellation of these traits, collectively called 'post‐dependent', emerges following brain exposure to repeated cycles of intoxication and withdrawal. The medial prefrontal cortex (mPFC) and its subdivisions exert top‐down regulation of approach and avoidance behaviors, including those that lead to alcohol intake. Here, we review an emerging literature which indicates that a reprogramming of mPFC function occurs with prolonged exposure of the brain to cycles of alcohol intoxication and withdrawal. This reprogramming results in molecular dysregulations that contribute to the post‐dependent syndrome. Convergent evidence has identified neuroadaptations resulting in altered glutamatergic and BDNF‐mediated signaling, and for these pathways, direct evidence for a mechanistic role has been obtained. Additional evidence points to a dysregulation of pathways involving calcium homeostasis and neurotransmitter release. Recent findings indicate that global DNA hypermethylation is a key factor in reprogramming the mPFC genome after a history of dependence. As one of the results of this epigenetic remodeling, several histone modifying epigenetic enzymes are repressed. Among these, PR‐domain zinc‐finger protein 2, a methyltransferase that selectively mono‐methylates histone H3 at lysine 9 has been functionally validated to drive several of the molecular and behavioral long‐term consequences of alcohol dependence. Information processing within the mPFC involves formation of dynamic neuronal networks, or functional ensembles that are shaped by transcriptional responses. The epigenetic dysregulations identified by our molecular studies are likely to alter this dynamic processing in multiple ways. In summary, epigenetic molecular switches in the mPFC appear to be turned on as alcoholism develops. Strategies to reverse these processes may offer targets for disease‐modifying treatments. Abstract : Post‐dependent reprogramming of transcriptome responses in the mPFC affects local cue‐responsive neuronal networks.